Estrangement and the somatics of literature : Tolstoy, Shklovsky, Brecht - Robinson, Douglas, 1954- (Parallax (Baltimore, Md.), 2008)
"Drawing together the estrangement theories of Viktor Shklovsky and Bertolt Brecht with Leo Tolstoy's theory of infection, Douglas Robinson studies the ways in which shared evaluative affect regulates both literary familiarity-convention and tradition-and modern strategies of alienation, depersonalization, and malaise." "Both a comparative study of Russian and German literary-theoretical history and an examination of the somatics of literature, this work provides a deeper understanding of how literature affects the reader and offers a new perspective on present-day problems in poststructuralist approaches to the human condition."--Jacket